Therapeutic pediatric nutrition - Sharma, Madhu Dietician; BNS Walia Emeritus Professor Pediatrics (New Delhi : Jaypee, 2011)
The book "Therapeutic Pediatric Nutrition" elucidates the dietetic management of common as well as uncommon diseases of childhood. Each chapter in this book gives complete information in every aspect of therapeutic dietetics and covers background, pathogenesis of factors leading to nutritional disorders, nutritional requirements in the particular disease entity and also dietary management. This book also entails the menu planning and development of recipes of all disorders in detail. The book has 21 chapters. The dietary management and nutrition support of several disorders such as diabetes mellitus, kidney disorders, celiac disease and enteral feeding are explained in detail. Rare disorders like inborn errors of metabolism are also covered in this book. Numerous tables in the text summarize the important recommendations. This book is found to be a useful guide for all trainers involved in the teaching of nutrition in colleges and other health care institutions.
1. Protein Energy Malnutrition 2. Dietary Modification in Childhood Obesity 3. Dietary Management in Malabsorption 4. Nutrition in Diarrheal Diseases 5. Diet in Celiac Diseases 6. Diet in Inflammatory Bowel Disease 7. Nutritional Support in Cystic Fibrosi 8. Diet in Constipation 9. Nutrition Support in Short Bowel Syndrome 10. Dietary Management in Fever and Infections 11. Nutrition Support in Juvenile Diabetes Mellitus 12. Dietary Management in Hypoglycemia 13. The Ketogenic Diet in Management of Epilepsy 14. Inborn Errors of Metabolism 15. Diet in Liver Diseases 16. Diet in Kidney Diseases 17. Enteral Nutrition in Hospitalized Patient 18. Nutritional Support of the Critically ILL Child 19. Nutrition in Childhood Cancer 20. Nutrition Support in Children with HIV/AIDS 21. Diet in Dental Health
Incluye índice
Incluye ilustraciones
Keywords: PEDIATRIC NUTRITION; THERAPEUTIC NUTRITIONAL; DIET